Data Analytics Capability Maturity and Governance Gaps in PT ABC: A Diagnostic Case Study - Simanjuntak, Almon Junior; Hidayanto, Achmad Nizar; Trimanadi, Raden (Indonesian Scientific Journal, 2026)
This study provides a within-case diagnosis of data analytics capability maturity in PT ABC to inform refinement of its 2025 to 2026 governance roadmap. Using a qualitative-first mixed-method diagnostic case design (QUALQUAN), this study conducted five semi-structured key-informant interviews first, followed by a cross-sectional survey of 76 purposively selected analytics-involved employees, analyzed using the Shortened TDWI Data Analytics Maturity Model (STDAMM). The overall maturity mean was 3.31 on a 5-point scale (bootstrap 95% confidence interval: 3.15 to 3.46), classifying the assessed respondent pool as Level 3 (Established). Dimension means were tightly clustered (3.27 to 3.35) with substantial confidence-interval overlap, suggesting that respondents perceive maturity as a coupled system rather than sharply separated capability domains. A small descriptive pattern places analytics use and infrastructure marginally above data management and organizational enablement, consistent with interview accounts of definition inconsistency, limited socialization of dictionary and stewardship practices, and recurring manual reconciliation of figures across systems. The findings support a governance-first refinement of the roadmap that prioritizes standardization and ownership mechanisms to improve the comparability and decision-readiness of analytics outputs, while treating subgroup comparisons cautiously where measurement comparability is not supported.